Short-term changes in the immune system of elite swimmers under competition conditions. Different immunomodulation induced by various types of sport - Espersen, G. T.; Elbaek, A.; Schmidt-Olsen, S.; Ejlersen, E.; Varming, K.; Grunnet, N. (Scandinavian Journal of Medicine & Science in Sports, 1996)
This study was designed to investigate changes in the immune system of elite swimmers compared with well-conditioned age- and sex-matched controls in relation to a competition swim (field study). Furthermore, the aim was to reveal possible differences in immune system changes depending on the type of sport performed by comparing with an earlier study of similar design, from the same laboratory that tested elite runners in relation to a competition run. The swimmers were tested before, immediately after and 2 h and 24 h after a competition swim. Lymphocyte subsets (CD5, CD3, HLA-DR, CD4, CD8, CD19, CD3/CD16+56, CD57, CD18, CD16/CD122) all increased after the run, decreased to normal or subnormal levels after 2 h, and returned to normal after 24 h (absolute numbers). The findings were identical for the swimmers and the age- and sex-matched control group. No change in polymorphonuclear granulocyte migration was found. The lymphocyte proliferative responses decreased 2 h after the exercise. No changes were seen in plasma cytokine levels (interleukin-1 beta (IL-1 beta), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-alpha) in relation to exercise, but significantly lower baseline values for IL-6 were observed in the swimmers. An increase in total natural killer cell activity immediately after exercise, followed after 2 h by a decrease, was seen in both swimmers and controls. Finally, no complement activation was detected. Compared with an earlier study of elite runners, differences were seen in granulocyte chemotactic response, TNF-alpha plasma activity and the lymphocyte proliferative response to mitogen. These differences might be explained by the degree of immune system activation following muscle damage during exercise, inducing an increase in cytokines, which are known to activate and modulate both lymphocytes and granulocyte function. Our findings demonstrate identical exercise-induced, immune system changes in elite swimmers and well conditioned controls, and furthermore, the findings suggest that different types of sport performed at maximum intensity induce different immune system changes. Scand J Med Sci Sports 1996 Jun;6(3):156-63